2009
DOI: 10.1124/dmd.109.029751
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Molecular Processing in the Hinge Region of Therapeutic IgG4 Antibodies on Disposition Profiles in Cynomolgus Monkeys

Abstract: ABSTRACT:The IgG4 isotype antibody is a potential candidate for immunotherapy when reduced effector functions are desirable. However, antigen binding fragment (Fab) arm exchange leads to functional monovalency with potentially reduced therapeutic efficacy. Mutagenesis studies suggested that the CH3 domain and not the core hinge is dominantly involved in in vivo molecular processing. This work investigated whether stabilization of the core hinge of a therapeutic IgG4 antibody by mutation of Ser228 to Pro ( Sinc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

6
54
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 43 publications
(60 citation statements)
references
References 12 publications
(20 reference statements)
6
54
0
Order By: Relevance
“…Therefore, mutations that completely prevent Fab-arm exchange in vivo should be considered when designing therapeutic IgG4 Abs. We and others have previously shown that a S228P mutation in the IgG4 corehinge represents a tool for preventing Fab-arm exchange to less than detection limits (8,9,15). The mutations in the CH3 domain identified in this article, R409K, R409L, R409M, K370E, and K370Q, may be used for additional stabilization or as an alternative approach to hinge stabilization.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Therefore, mutations that completely prevent Fab-arm exchange in vivo should be considered when designing therapeutic IgG4 Abs. We and others have previously shown that a S228P mutation in the IgG4 corehinge represents a tool for preventing Fab-arm exchange to less than detection limits (8,9,15). The mutations in the CH3 domain identified in this article, R409K, R409L, R409M, K370E, and K370Q, may be used for additional stabilization or as an alternative approach to hinge stabilization.…”
Section: Discussionmentioning
confidence: 99%
“…3). Previous studies suggested that IgG from rhesus monkeys (Macaca mulatta) (6), cynomolgus monkeys (Macaca fascicularis) (8,9), and IgG3 from mice (Mus musculus) (8) could engage in Fab-arm exchange with human IgG4. In accordance, we now demonstrate that a variety of other species share this ability.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A large variety of formats for bispecific antibodies has been described (1-3). The most prominent examples are tetravalent IgG-single-chain variable fragment (scFv) fusions (4-6), catumaxomab, a trifunctional rat/mouse hybrid bispecific epithelial cell adhesion molecule-CD3 antibody (7), the bispecific CD19-CD3 scFv antibody blinatumomab (8), "dualacting Fab" (DAF) antibodies (9), tetravalent bispecific formats such as the IgG-like dual-variable-domain antibodies (DVD-Ig) (10), covalently linked pharmacophore peptides to catalytic antibodies (11), or use of the dynamic exchange between half IgG4 molecules to generate bispecific antibodies (12,13). Each of these approaches has advantages but also has limitations such as immunogenicity, poor pharmacokinetic properties, or loss of effector functions caused by the lack of a fragment crystallizable (Fc) region; also, they may tend to aggregate because of the presence of linkers or may contain potentially immunogenic nonhuman domains.…”
mentioning
confidence: 99%